HYPOTROPHY OF THE HEART AND REDUCTION OF INTRACARDIAC HEMODYNAMICS IN LOW BLOOD PRESSURE IN YOUNG WOMEN - V. M. Baev; E. N. Kudryavoeva; O. A. Igumnova; T. YU. Agafonova; E. A. Vagner (Евразийский Кардиологический Журнал)
The aim of the study was to study echocardiographic parameters in young women with idiopathic arterial hypotension (IAH).